Occurrence Survey of the Sulawesi Giant Squirrel (Rubrisciurus rubriventer) in Five Buffer Villages around Gandang Dewata National Park - Ririn Ririn; Muhammad Rizaldi Trias Jaya Putra Nurdin; Yusrianto Nasir; Maipa Dia Pati (Center for Ecology, Conservation and Ethnobiology Studies, Universitas Sulawesi Barat, 2025)
This study aimed to examine the occurrence of the Sulawesi Giant Squirrel (Rubrisciurus rubriventer) in five buffer villages surrounding Gandang Dewata National Park and to evaluate its potential as a biological learning resource. The research employed a quantitative descriptive approach through a survey of 66 respondents distributed across Rambusaratu, Taupe, Mambulilling, Tondok Bakaru, and Lambanan villages. The results showed that 92.42% of respondents reported having directly observed the Sulawesi Giant Squirrel, with the highest distribution reported in Rambusaratu and Mambulilling villages. The use of squirrels by local communities is predominantly for consumption (56%), while the remaining respondents either do not utilize the species or are unaware of its use. In addition, validation results of a booklet developed as a learning medium based on field findings indicated a very high level of validity (score ≥ 4.8), suggesting that it is suitable for use in learning activities based on local potential. This study highlights the importance of utilizing local biodiversity to support contextual learning and the conservation of endemic species